Analysis of the relationship of land carrying capacity and building area towards the development of Kualanamu International Airport in 2010 and 2017 - Aprillia Christianawati; Fitri Riswari Prima; Seri Aryati; Ghina Salsabila; Muthia Hasna Thilfatantil (Brawijaya University, 2020)
Land resources availability has been declining due to the rapid development of the industrial, residential, and even tourism sectors in all regions, including Batang Kuis Subdistrict, Deli Serdang Regency of North Sumatra Province. The declining of land resources in Batang Kuis Subdistrict has a strong relationship with the factors causing rapid and dynamic development of Kualanamu Airport located at the east side of the sub-district. Regional development causes land conversion and urban development that impacts on carrying capacity of the land. Therefore, the objective of this study was to determine the relationship between land use and land carrying capacity of Batang Kuis Subdistrict in 2010 and 2017. Data used for this study consisted of primary data by Google Earth satellite imagery of Batang Kuis Subdistrict and secondary data of population and area per village in 2010 and 2017. The analysis used for this study was a quantitative analysis by calculating Land Carrying Capacity (LCC) and spatial analysis by mapping the land area that has been developed in two years with a unit of analysis at the village. Results obtained from this study were land carrying capacity table and the land area maps of Batang Kuis Subdistrict for 2010 and 2017. The highest value of land consumption per capita referring to Yeates dan Garner standard was observed at Sena, Sidodadi, and Mesjid Villages in 2010 and 2017. The main factor is easy accessibility since the development of Kualanamu Airport.